Characteristics of the spatio-temporal evolution of the improved integrated ecological effect index (IEEI) in mountainous province based on remote sensing: a case study in Yunnan province of southwest China - Yang, Renyi; Yang, Zisheng; Zhong, Changbiao; He, Yimei (Frontiers in Ecology and Evolution, 2024)
Land use/cover change (LUCC) and the evaluation of its ecological effects are the important and key areas of research on global environmental change and sustainable development. In response to the problems and limitations of various methods of evaluating the ecological effects of LUCC, this article takes Yunnan Province, a mountainous province with a relatively fragile “innate” ecological environment, as the research area. Based on LUCC data from the interpretation of seven phases of remote sensing (RS) images taken in Yunnan, combined with the investigation of soil erosion data by using remote sensing technology, an improved integrated ecological effect index (IEEI) for the LUCC and a method for its evaluation are proposed; this index was applied to calculate the integrated ecological effect index for the LUCC and analyze its spatiotemporal evolution in 129 counties in Yunnan from 1990 to 2020. The spatiotemporal changes, characteristics, and laws of the integrated ecological effects of LUCC in the whole province and counties from 1990 to 2020 were revealed, with the goal of offering a fundamental framework for long-term strategic planning and management in mountainous provinces. Overall, in the past 30 years, the integrated ecological effect of Yunnan Province and various counties has significantly improved. However, the IEEI of the province is not yet very high, and its regional differences are significant. It is urgent to increase the efforts of ecological civilization construction (ECC) throughout the province, adopt practical and effective ecologically-friendly land use ways and ecological environment protection and construction measures according to local conditions, and steadily improve the integrated ecological effect of various regions.